2021
DOI: 10.3390/pharmaceutics13030407
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Cross-Linking as a Strategy to Modulate the Properties of Oral Mucoadhesive Microparticles Based on Polysaccharide Blends

Abstract: Polymer blends of gellan gum (GG)/retrograded starch(RS) and GG/pectin (P) were cross-linked with calcium, aluminum, or both to prepare mucoadhesive microparticles as oral carriers of drugs or nano systems. Cross-linking with different cations promoted different effects on each blend, which can potentially be explored as novel strategies for modulating physical–chemical and mucoadhesive properties of microparticles. Particles exhibited spherical shapes, diameters from 888 to 1764 µm, and span index values lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…LA gellan occurs as a result of the effect of alkaline hydrolysis. The LA gellan is broadly investigated as a component of oral drug delivery systems with the sustained or modified release [ 19 , 20 , 21 , 22 ]. In practice, the encapsulation of drugs into gellan gum matrices can be performed in two ways.…”
Section: Introductionmentioning
confidence: 99%
“…LA gellan occurs as a result of the effect of alkaline hydrolysis. The LA gellan is broadly investigated as a component of oral drug delivery systems with the sustained or modified release [ 19 , 20 , 21 , 22 ]. In practice, the encapsulation of drugs into gellan gum matrices can be performed in two ways.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MPs could improve the water solubility of poorly soluble drugs, enhance their bioavailability, ensure controlled and sustained drug release (Khalifa and Abdul Rasool, 2017), and decrease drug toxicity (Oliveira et al, 2017). It was found that these carriers were promising in drugs protection and improving their stability (Boni et al, 2021), targeting the drug to a specific biological site, and reducing the number of doses, thereby improving patient adherence to treatment (Abdul Rasool et al, 2014;Bartos et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recent advancements in microparticle manufacturing technology include procedures such as membrane emulsification (ME) [28], active self-healing encapsulation (ASE) [10], and micromechanical punching (MMP) for the fabrication of non-spherical microparticles [29]. Finally, ionotropic cross-linking [29], [30] and LbL-assembly [31], [32] are commonly used strategies in polysaccharide-based micro-sized drug delivery systems.…”
mentioning
confidence: 99%